2020
DOI: 10.1007/s40200-020-00670-6
|View full text |Cite
|
Sign up to set email alerts
|

Swimming training attenuates pancreatic apoptosis through miR-34a/Sirtu in1/P53 Axis in high-fat diet and Streptozotocin-induced Type-2 diabetic rats

Abstract: Objective The present study sought to evaluate the miR-34a/Sirtuin1/p53 pro-apoptotic pathway, and reveal its modulation in diabetic rats undergoing swimming exercise. Methods Twenty-eight male Wistar rats were divided into four groups. They were inducted to develop diabetes by injection of streptozotocin. After 12 weeks of swimming, the pancreatic tissue of these rats were removed to be evaluated for the expression level of Sitruin1/P53/miR-34a through qPCR. Results Findings indicated a marked rise in the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…In some studies, the level of P53 expression is increased, 32 , 33 but others reported a decreased in P53 after exercise. 34 , 35 However, in the present study, the level of P53 remained unchanged compared to pre-exercise leves, which is in line with the obervations of Alipour et al 36 and Sadeghi- Tabas et al 37 One of the reasons that cytochrome C and P53 expression remained unchanged in the present study was that the subjects in this study were healthy young rats. However, previous studies used old, ovariectomized, or diabetic rats, and the rate of apoptosis and cell death in these subjects are higher due to the oxidative stress and inflammatory factors, compared to the healthy young subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In some studies, the level of P53 expression is increased, 32 , 33 but others reported a decreased in P53 after exercise. 34 , 35 However, in the present study, the level of P53 remained unchanged compared to pre-exercise leves, which is in line with the obervations of Alipour et al 36 and Sadeghi- Tabas et al 37 One of the reasons that cytochrome C and P53 expression remained unchanged in the present study was that the subjects in this study were healthy young rats. However, previous studies used old, ovariectomized, or diabetic rats, and the rate of apoptosis and cell death in these subjects are higher due to the oxidative stress and inflammatory factors, compared to the healthy young subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Alveolar cells that are large 22 . The content of this plant from the Karo tribe is responsible for lung tissue that begins to improve as a result of excessive swimming 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although intrinsic and extrinsic apoptosis has different beginnings, both of them conclude with the activation of the caspase family of cysteine proteases 23 . Caspases (such as caspase 8 or 9) start a cascade of proteolytic events that result in the activation of executioner caspases 24,25 . Numerous substrates are broken down by caspases, which also cause DNA breakage, phosphatidylserine exposure and organelle enzymatic destruction 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Alipour et al investigated the decrease in miR-34 in response to physical exercise; they showed for the first time the negative effect of swimming exercise on the expression of miR-34 on pancreatic tissue of mice with type 2 diabetes; in general, these findings displayed the modulation through physical activity on molecular axis miR-34/SIRT1/P53 [68]. Previous studies demonstrated that SIRT1 increased in response to physical activity, causing protective anti-apoptotic markers.…”
Section: Physical Activity and Mirnas Modulation In Prevent Of Bone L...mentioning
confidence: 99%